The Interobjectivity of the Wind in the Prose of Bruno Schulz - Tomczok, Paweł (Porównania, 2022)
The aim of the article is to discuss the wind in the prose of Bruno Schulz. The category of a hyperobject proposed by Timothy Morton was used to interpret the problem, as well as the assumptions of object-oriented ontology. Recalling this philosophy made it possible to notice in Schulz’s prose fragments presenting the environment, especially the wind, in the urban space. The writer ascribes various meanings to the described atmospheric phenomena—they serve him to build an atmosphere of danger, but also to outline a utopia of peace and tranquillity.